Pengenalan Tentang Perkembangan “TIK” Sebagai Pembelajaran Dan Pembentukan Cita-Cita Siswa Pondok Pesantren Nafidatunnajah - Deni Setiandika; Dewi Yanti Angreani B. S; Kifco Anggi Ramadhan; Muhammad Affuan; Muhammad Iskandar; Muhammad Rizky F; Muhammad Usman A. J; Nursyah Pratiwi; Sholahuddin; Syahrul Alifianda (AMMA : Jurnal Pengabdian Masyarakat, 2023)
As time goes by and the rapid development of today's technology, almost all aspects of life use the internet. It becomes important for every individual including students to get to know about the internet and technology. Students are people who come to an institution to obtain or study some type of education. At this time, students experience various changes, both physical and psychological. Apart from that, they also change cognitively and begin to break away emotionally from their parents in order to carry Out their new social roles as adults, one of which is work. Improving the competence, quality and competitiveness of students is a must in facing this digital era, operating a computer is part of the hard skills. Students need to have skills and insight into some of the ideals and professions in the TIK field. The purpose of this activity is to provide education for students about various professions in the field of TIK so that students can increase motivation, competence, quality, and competitiveness of Class 9 Middle School Students at Nafidatunnajah Islamic Boarding School when entering the future. The results of the dedication at Nafidatunnajah Islamic Boarding School can be concluded that this service activity is right on target and can provide benefits for students, and provide more knowledge about TIK.